THIRD PLACE AND NOSTALGIA IN POSTCOLONIAL JAKARTA: ADAPTIVE REUSE OF CIKINI POST OFFICE - Fajarwati, Ade Ariyani Sari; Aviandy, Mochamad (UI Scholars Hub, 2025)
The transformation of space in postcolonial cities extends beyond the restoration of old buildings; it involves cultural practices that reshape collective memory and identity. Through adaptive reuse, colonial-era heritage spaces are revitalised as social hubs. This study examines Post Kantoor cafe, a former colonial post office turned into a “third place” within urban spatial culture. Using qualitative methods—visual observation, spatial documentation, and a literature review—the study finds that nostalgic aesthetics, evident in antique artefacts, colonial atmospheres, and curated visuals, foster emotional connections across generations and social classes. More than a site of consumption, the cafe becomes a space for dialogue, cultural exchange, and reinterpretation of history. These findings show that adaptive reuse in postcolonial contexts can produce inclusive, meaningful spaces rich in cultural symbolism.